2022
DOI: 10.3390/pharmaceutics14071387
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Induction of Antigen-Specific CD8+ T-Cell Responses by Cationic Peptide-Based mRNA Nanoparticles

Abstract: A major determinant for the success of mRNA-based vaccines is the composition of the nanoparticles (NPs) used for formulation and delivery. Cationic peptides represent interesting candidate carriers for mRNA, since they have been shown to efficiently deliver nucleic acids to eukaryotic cells. mRNA NPs based on arginine-rich peptides have previously been demonstrated to induce potent antigen-specific CD8+ T-cell responses. We therefore compared the histidine-rich amphipathic peptide LAH4-L1 (KKALLAHALHLLALLALHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…Moreover, cationic peptides as candidate carriers for mRNA have been shown to efficiently deliver nucleic acids to eukaryotic cells. A cationic peptide-based mRNA nanoparticles could induce efficient antigenspecific CD8 + T cell responses [88]. Peptide-based mRNA delivery systems show promise in the field of gene therapy, enabling the delivery of therapeutic mRNA to correct genetic disorders.…”
Section: Protein-based Mrna Delivery Systemmentioning
confidence: 99%
“…Moreover, cationic peptides as candidate carriers for mRNA have been shown to efficiently deliver nucleic acids to eukaryotic cells. A cationic peptide-based mRNA nanoparticles could induce efficient antigenspecific CD8 + T cell responses [88]. Peptide-based mRNA delivery systems show promise in the field of gene therapy, enabling the delivery of therapeutic mRNA to correct genetic disorders.…”
Section: Protein-based Mrna Delivery Systemmentioning
confidence: 99%
“…Among those CPPs, the cationic amphipathic histidine-rich LAH4 family stood out for its ability to transport a variety of cargoes including DNA [23][24][25], siRNA [26], proteins [27], peptide antigens [28], retroviruses [29][30][31], adeno-associated viruses [32], and quantum dots [33]. Now, in addition to those delivery capabilities, two recent reports showed that the LAH4-L1-derived LAH4 peptide also possesses mRNA delivery capacities [34,35]. Moreover, in 2023, Xu et al reported that a PEGylated LAH4-L1 peptide (PEG 12 -LAH4-L1) efficiently delivers mRNA into tumor cells [36].…”
Section: Introductionmentioning
confidence: 99%